2020
DOI: 10.1200/jco.2020.38.4_suppl.574
|View full text |Cite
|
Sign up to set email alerts
|

NTRK gene fusions in biliary tract cancers.

Abstract: 574 Background: Gene fusions involving one of the 3 neurotrophic tyrosine receptor kinases ( NTRK) have been identified in approximately 1% of solid tumors and inhibitors of TRK (e.g. larotrectinib) have been shown to have anti-tumor activity regardless of tumor type. NTRK gene fusions have been previously reported in bilio-pancreatic cancers. It is of interest therefore to determine the incidence and molecular characteristics of NTRK gene fusions in patients with bilio-pancreatic cancers. Methods: Formalin-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The comprehensive genomic profiling of Chinese BTC patients has not been well elucidated and is needed to be investigated in large cohorts. Furthermore, NTRK fusions occurring in 0.75% of patients with BTC, 34 were not observed in this cohort. Somatic mutations were detected in 71.4% of bile cfDNA samples, whereas these were identified in only 53.6% of plasma cfDNA samples in this study.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The comprehensive genomic profiling of Chinese BTC patients has not been well elucidated and is needed to be investigated in large cohorts. Furthermore, NTRK fusions occurring in 0.75% of patients with BTC, 34 were not observed in this cohort. Somatic mutations were detected in 71.4% of bile cfDNA samples, whereas these were identified in only 53.6% of plasma cfDNA samples in this study.…”
Section: Discussionmentioning
confidence: 57%
“…The comprehensive genomic profiling of Chinese BTC patients has not been well elucidated and is needed to be investigated in large cohorts. Furthermore, NTRK fusions occurring in 0.75% of patients with BTC, 34 were not observed in this cohort.…”
Section: Discussionmentioning
confidence: 57%
“…NTRK fusions have recently emerged as interesting driver mutations for cancer treatment, which have been detected in adult and pediatric cancers [ 113 ]. In BTC, the reported percentage of NTRK fusions was 0.75% [ 114 ]. Larotrectinib (LOXO-101) and entrectinib (RDX-101) are first-generation, potent and highly selective pan-TRK inhibitors that were approved by the FDA, for pediatric and adult patients with refractory solid tumors harboring NTRK gene that progressed after standard treatments without suitable alternative treatments [ 115 ].…”
Section: Ntrkmentioning
confidence: 99%
“…It has also been reported that these fusion genes tend to be found in younger patients. There are some case reports showing the effects of inhibitors targeting these genetic abnormalities [117][118][119][120][121].…”
Section: Rare Fusion Genesmentioning
confidence: 99%